2016
DOI: 10.4236/ojbd.2016.64011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time and Temperature Variables on Some Routine Coagulation Tests among Subjects of African Descent in Sokoto, North Western Nigeria

Abstract: This study evaluated the effects of time and temperature variables on routine Prothrombin Time test and Activated Partial Thromboplastin Time (APTT) test among subjects of African descent in Sokoto, North Western Nigeria. Samples of 99 subjects made up of 49 male and 50 female subjects with mean age 38.3 ± 22.3 years. Coagulation tests were performed immediately specified times after phlebotomy up to 24 hours (0, 1, 2, 3, 4 and 24 hours at room temperature of 40 degrees C. Our data demonstrate that prothrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…6 In a similar study by Ikhuenbor et al prothrombin time (PT) & activated partial thromboplastin time (APTT) results were stable for upto 2 hours and remaining constant regardless of storage conditions. 7 Kemkes-Matthes et al In his study concluded that the acceptable storage time can be extended to 24 h for PT. 8 Adcock et al in his study demonstrated that PT results are stable for upto 24 h, remaining constant regardless of storage conditions.…”
Section: Discussionmentioning
confidence: 97%
“…6 In a similar study by Ikhuenbor et al prothrombin time (PT) & activated partial thromboplastin time (APTT) results were stable for upto 2 hours and remaining constant regardless of storage conditions. 7 Kemkes-Matthes et al In his study concluded that the acceptable storage time can be extended to 24 h for PT. 8 Adcock et al in his study demonstrated that PT results are stable for upto 24 h, remaining constant regardless of storage conditions.…”
Section: Discussionmentioning
confidence: 97%
“…[11,12]. Ikhuenbor et al concluded that a longer timing (after two hours) from phlebotomy showed a statistically significant increase in the PT and APTT results [3].…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin time (PT) and activated partial thromboplastin time (APTT) are commonly used coagulation tests to assess pathological changes in hemostasis and coagulation systems [1,2]. In addition, the international normalized ratio (INR) is used to monitor oral anticoagulant therapy for reducing the risk of thromboembolic events and minimizing the incidence of bleeding complications [3]. The laboratory testing process is partitioned into three phases, namely, pre-analytical, analytical, and post-analytical phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation